Giant Abdominoperineal Malignant Schwannoma: An Unusual Presentation and Surgical Challenge. (2nd April 2015) - Panwar, Pankaj; Kumar, Santosh; Singh, Shivanshu; Sriharsha, Ajjoor Shankargowda; Gupta, Kirti
Abstract : Schwannoma is a benign tumor arising from the Schwann cells of peripheral nerves. These are usually benign but malignant transformation can occur in larger lesions. The definitive diagnosis of malignancy can only be made after final histopathological report. The literature reports large pelvic and perineal schwannomas with few being malignant. We report the first case of such giant malignant abdominoperineal schwannoma which was benign on initial biopsy but final histopathology revealed it to be malignant. In view of proximity of perineal and pelvic tumors to urogenital organs and pelvic nerves, such cases represent a challenge to surgical excision. This case brings to highlight another atypical presentation of such tumors.